2010
DOI: 10.1016/j.ejpain.2009.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic pattern of PCA opioid demand in adults with cancer pain

Abstract: PCA met individual patient's opioid needs in a safe and effective manner despite a large inter-individual variability in opioid consumption. Moreover, the study indicated a pattern of less opioid requirement at night.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Next, Kavaliers et al also demonstrated that the change of daily rhythms alters the analgesia of morphine in mice, with an enhanced analgesic effect in the dark cycle [ 12 ]. A clinical retrospective study observed a lower demand for self-administered morphine in adults with cancer pain at night [ 13 ]. Furthermore, morphine showed considerable pharmacokinetic variation depending on the time of injection during the day [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Next, Kavaliers et al also demonstrated that the change of daily rhythms alters the analgesia of morphine in mice, with an enhanced analgesic effect in the dark cycle [ 12 ]. A clinical retrospective study observed a lower demand for self-administered morphine in adults with cancer pain at night [ 13 ]. Furthermore, morphine showed considerable pharmacokinetic variation depending on the time of injection during the day [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, studying analgesic consumptions is difficult, analgesic consumptions of acute pain differ across not only the patients but also time. 8 , 9 Although the evidence showed patterns of morphine reduction from postoperative day 1 to day 3 and a possible biological rhythm pattern existing, 5 , 10 , 11 studies to reveal the analgesic patterns are very rare. 10 , 11 …”
mentioning
confidence: 99%
“…Cancer pain sufferers appear to experience more breakthrough pain (BTP) during the late morning around 9:45 -10:15 (Saini et al, 2012). Consistent with these results, Schiessl et al (2010), evaluated the use of an opioid-PCA for the treatment of BTP in adults with cancer pain. They found that opioid analgesia was least demanded from 22:00 to 6:00 compared to any other time of the day with a significant 34% less self-administered opioid within these hours.…”
Section: Circadian Rhythm In Pain Perceptionmentioning
confidence: 68%